2012
DOI: 10.2519/jospt.2012.3988
|View full text |Cite
|
Sign up to set email alerts
|

The Validity of Upper-Limb Neurodynamic Tests for Detecting Peripheral Neuropathic Pain

Abstract: Synopsis The validity of upper-limb neurodynamic tests (ULNTs) for detecting peripheral neuropathic pain (PNP) was assessed by reviewing the evidence on plausibility, the definition of a positive test, reliability, and concurrent validity. Evidence was identified by a structured search for peer-reviewed articles published in English before May 2011. The quality of concurrent validity studies was assessed with the Quality Assessment of Diagnostic Accuracy Studies tool, where appropriate. Biomechanical and exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
75
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(91 citation statements)
references
References 123 publications
(159 reference statements)
1
75
0
9
Order By: Relevance
“…Currently, to our knowledge, no study has documented the normal responses of the ulnar upperlimb neurodynamic test (ULNT3). 28 In a case report described by Shacklock, 36 an association between improvement of the ULNT3 response and a decrease in symptoms was found in a patient with surgically confirmed ulnar neuropathy.…”
Section: T T Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, to our knowledge, no study has documented the normal responses of the ulnar upperlimb neurodynamic test (ULNT3). 28 In a case report described by Shacklock, 36 an association between improvement of the ULNT3 response and a decrease in symptoms was found in a patient with surgically confirmed ulnar neuropathy.…”
Section: T T Conclusionmentioning
confidence: 99%
“…6,13,26 Finally, recent evidence asserts that a positive upper-limb neurodynamic test should at least partially reproduce the patient's symptoms, and structural differentiation should change these symptoms. 28 This latter definition of a positive upper-limb neurodynamic test has been shown to be reliable when used clinically. 28 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7,19 This ULNT-1 MEDIAN response suggested that participants' symptoms were at least partly related to increased nerve mechanosensitivity in the neck and upper limb. 7,25,50 Participants with 2 or more abnormal neurological signs (decreased strength, reflex, or sensation) at the same nerve root level (C5-T1) were excluded. 65 It has been suggested that these 2 enrollment criteria would select participants who would be considered appropriate candidates for NTM.…”
Section: Participantsmentioning
confidence: 99%
“…Neurodynamics is the concept based on a close interaction of mechanics and physiology of the nervous system which is to be considered while assessing and treating patients via nervous system mobilization and manual therapy [123]. Neurodynamic testing had been validated for its use in detecting peripheral neuropathic pain [124], and it was Boyd et al [125] demonstrated diminished mechanosensitivity of lower extremity peripheral nerves in individuals with peripheral neuropathy.…”
Section: Manual Therapymentioning
confidence: 99%